1998
DOI: 10.1021/ja980387u
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Mimetics Obtained by Novel, Rapid Screening of Carboxylic Acid Encoded Glycopeptide Libraries

Abstract: Glycopeptides that mimic the action of oligosaccharides have been rapidly identified through the implementation of combinatorial library methodology combined with a novel, easy, screening and analysis method. A glycopeptide library containing three different glycosyl amino building blocks, Fmoc-Asn(β-Ac3GlcNAc)-OPfp (5), Fmoc-Thr(α-Ac4Man)-OPfp (6), and Fmoc-Thr[α-Ac4Man(1→3)α-2-O-Bz-4,6-Ac2Man]-OPfp (7), was synthesized by the portion-mixing method on PEGA solid support. The library was designed to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 40 publications
(61 reference statements)
1
49
0
3
Order By: Relevance
“…Siuzdak and Lewis have demonstrated that peptides and carbohydrates, covalently linked to a polymeric support through a photolabile linker, can be directly identified by MALDI in a single step that requires no pretreatment of the sample to induce cleavage from the support [42]. In another application [43], MALDI was used for photolytic release and determination of an active glycopeptide from the resin support. The resulting mass spectral data contained the ladder of glycopeptide fragments and yielded the active glycopeptide sequence.…”
Section: Qualitative Characterization Of Lmw Compoundsmentioning
confidence: 99%
“…Siuzdak and Lewis have demonstrated that peptides and carbohydrates, covalently linked to a polymeric support through a photolabile linker, can be directly identified by MALDI in a single step that requires no pretreatment of the sample to induce cleavage from the support [42]. In another application [43], MALDI was used for photolytic release and determination of an active glycopeptide from the resin support. The resulting mass spectral data contained the ladder of glycopeptide fragments and yielded the active glycopeptide sequence.…”
Section: Qualitative Characterization Of Lmw Compoundsmentioning
confidence: 99%
“…12 We pursued an approach in which we aim to identify peptides that can serve as a moiety that synergizes with glycans in binding to lectins (Figure 1), rather than acting as a neutral linker or standalone recognition element. Indeed, synthetic conjugates of peptides and carbohydrates are known to yield effective inhibitors of carbohydrate–protein interactions, 13 but the throughput of synthesis of these ligands is limited. Here, we employ genetically encoded fragment-based discovery (GE-FBD) to identify peptide fragments (Figure 1) capable of forming a synergistic interaction together with a glycan moiety by taking advantage of the immense diversity of a genetically encoded peptide library.…”
mentioning
confidence: 99%
“…These results suggest that the adduct product is modified into the dehydrated specie when exposed to the laser during ionisation in the MALDI instrument. The ability of the MALDI's Nd:YAG laser to induce photochemical reaction has been shown and used by a few groups for synthesis monitoring and structural elucidation of biomolecules [10,11]. MS/MS analysis of the dehydrated product molecular ion yielded high-quality spectra from which the linearized peptide 4 could be unambiguously sequenced manually and by using de novo sequencing with the Peaks software (Figure 3b) [12].…”
Section: Fig 1 Synthetic Route To Cyclic Peptides With Anp Residue mentioning
confidence: 99%